ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Dhesti Widya Nurhasanah Ningrum; Irma Hermayanty (Universitas Padjadjaran, 2018)
This research entitled Analysis of Society Satisfaction Index on Public Service Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumedang. The aim of this study is to determine the level of Sumedang's society satisfaction to provided services by the Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumedang.The population of this study is the community of Sumedang who got the service in Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumedang. The sampling technique used simple random sampling. Result of sample drawing calculation, got the number of sample are 150 responden. The analytical technique used to test the research hypothesis is quantitative analysis using the formula of IKM (Indeks Kepuasan Masyarakat/ Satisfaction Index of Society) consisting of 14 elements of service.The results of the research indicate that the overall service provided by the Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumedang is 75.615 which are in the category of Good. The value for the average on each service element is as follows: 3.140 for service procedure element, the service requirement element is 3,027, the clarity of the service officer is 3,040, the disciplinary element of the service officer is 3,033, the service responsibility element is 3,020, is 3,040, element of service speed is 3,007, element of justice to get service is 3,020, politeness element and hospitality officer is 3,027, service cost element is 3,047, element certainty service cost is 3,027, element certainty service schedule is 3,047, and the security element of the service is 3,073.